Seismic status in Bangladesh - Rahman, Syed Mustafizur; Rahman, Md. Habibur; Faruk, Md. Omar; Islam, Md. Sultan-Ul (Vietnam Journal of Earth Sciences, 2018)
Seismic status in Bangladesh has been investigated using earthquake data recorded by the global network of USGS during 1980 to 2016. Seismicity parameters such as magnitude completeness Mc, b-value and a-value are being estimated. It has observed that the overall b-value in and around Bangladesh is of 0.84 which is seemed to be seismically active zone. As, reliable b-value assessment can lead to better seismic hazard analysis, reliable magnitude of completeness Mc can lead to b-value assessment of an area, this work has dealt and estimated magnitude of completeness Mc using various techniques for the whole region for a reliable estimation. Estimated Mc is obtained to be around 3.9-4.7, which lead to b-value of 0.93. Spatial variations of Mc and b-value have been investigated for 1ox1o horizontal and vertical rectangular regions for the study area between 18-29°N and 84-95°E. Estimated Mc and b-value along with b-value are then averaged for the common regions in the pair of horizontal and vertical regions. Results are then being presented in the form of maps. The findings resemble as, the Mc is low at the border line of N-W Bangladesh, and a line from Cox’s bazaar to Sylhet through Hill tracts. Remain parts belong to the Mc value of 4.1-4.2, thus the b-value obtained is varying from 0.68 to 1.2, where, the value is higher at region in Chittagong and Barisal division that extends toward north through part of Dhaka to Sylhet and lower at Rajshahi, Rangpur and part of Khulna division, while a-value is varying from 5.0 to 7.2 mostly from west to east. References Abercrombie R.E., and Brune J.N., 1994. Evidence for a constant b-value above magnitude 0 in the southern San Andreas, San Jacinto, and San Miguel fault zones and at the Long Valley caldera, California. Geophys. Res. Lett., 21(15), 1647-1650. Aki K., 1965. Maximum likelihood estimate of b in the formula log N=a-b M and its confidence limits. Bull. Earthquake Res Inst., Tokyo Univ., 43, 237-239. Aki S., 1987. On nonparametric tests for symmetry. Ann. Inst. Statist. Math., 39, 457-472. Al-Hussaini T.M., 2006. Seismicity and Seismic Hazard Assessment in Bangladesh: Reference to Code Provisions. Meeting on Seismic Hazard in Asia ICTP, Trieste, Dec. 4-8. Amorese D., 2007. Applying a change-point detection method on frequency-magnitude distributions. Bull. Seismol. Soc. Am., 97(5), 1742-1749. Doi:10.1785/0120060181. Banglapedia, 2012. The National Encyclopedia of Bangladesh. http://en.banglapedia.org/index.php?title=Tectonic_Framework, retrieved on 31 Aug 2017. Cao A.M., and Gao S.S., 2002. Temporal variations of seismic b-values beneath northeastern Japan island arc. Geophys. Res. Lett., 29(9), 481-483. Doi:10.1029/2001GL013775. Das R., Wason H.R., and Sharma M.L., 2012. Temporal and spatial variations in the magnitude of completeness for homogenized moment magnitude catalogue for northeast India. J. Earth Syst. Sci., 121(1), 19-28. Felzer K.R., 2008. Simulated aftershock sequences for a M 7.8 earthquake on the southern San Andreas fault. Seismol. Res. Lett., 80, 21-25. GSB, 2018. Seismic Zone Map of Bangladesh. http://gsb.portal.gov.bd/sites/default/files/files/gsb.portal.gov.bd/common_document/a6e75ad2_5acd_4fe3_911d_c9d25a7e349e/BD_Sciesmic-zonemap(NBC).pdf, retrieved on 31 March 2018. Gutenberg B., and Richter C.F., 1944. Frequency of earthquakes in California, Bull. Seismol. Soc. Am., 34, 184-188. Gutenberg B., and Richter C.F., 1956. Earthquake magnitude, intensity, energy and acceleration (second paper). Bull. Seismol Soc. Am., 46(2), 105-145. Hafiez H.E.A., 2015. Estimating the magnitude of completeness for assessing the quality of earthquake catalogue of the ENSN. Egypt. Arab J. Geosci., 8(1), 9315-9323. Doi:10.1007/s12517-015-1929-x. Hunting Geology and Geophysics Ltd., (1981), Interpretation and Operations report on an aeromagnetic survey in Bangladesh, Borehamwood, Hertfordshire, England. Iwata T., 2008. Low detection capability of global earthquakes after the occurrence of large earthquakes: investigation of the Harvard cmt catalogue. Geophys. J. Int., 174(3), 849-856. Doi:10.1111/j.1365-246X.2008.03864.x. Kagan Y.Y., 2002. Seismic moment distribution revisited: I. statistical results. Geophys. J. Int., 148(3), 520-541. Doi: 10.1046/j.1365-246x.2002.01594.x. Khan P.K., Ghosh M., Chakraborty P.P., and Mukherjee D., 2011. Seismic b-Value and the Assessment of Ambient Stress in Northeast India. Pure Appl. Geophys., 168(10), 1693-1706. Doi:10.1007/s00024-010-0194-x. Kolathayar S., Sitharam T.G., and Vipin K.S., 2012. Spatial variation of seismicity parameters across India and adjoining areas. Nat Hazards, 60(3), 1365-1379. Doi:10.1007/s11069-011-9898-1. Lomnitz-Adler J., and Lomnitz C., 1979. A modified form of the Gutenberg-Richter magnitude-frequency relation. Bull. Seism. Soc. Am., 69(4), 1209-1214. Marsan D., 2003. Triggering of seismicity at short timescales following Californian earthquakes. J. Geophys. Res., 108, B5, 2266. Doi:10.1029/2002JB001946. Mignan A., 2011. Retrospective on the Accelerating Seismic Release (ASR) hypothesis: Controversy and new horizons. Tectonophysics, 505(1), 1-16. Doi:10.1016/j.tecto.2011.03.010. Mignan A., and Woessner J., 2012. Estimating the magnitude of completeness for earthquake catalogs, Community Online Resource for Statistical Seismicity Analysis. Swiss Seismological Service, ETH Zurich, 145p. Doi:10.5078/corssa-00180805. Available at http://www.corssa.org. Naylor M., Orfanogiannaki, K., and Harte D., 2010. Exploratory data analysis: magnitude, space, and time. Community Online Resource for Statistical Seismicity Analysis, 42p. Doi:10.5078/corssa-92330203. Available at http://www.corssa.org. Ogata Y., and Katsura K., 1993. Analysis of temporal and spatial heterogeneity of magnitude frequency distribution inferred from earthquake catalogues. Geophys. J. Int., 113(3), 727-738. Doi:10.1111/j.1365-246X.1993.tb04663.x. Ogata Y., and Katsura K., 2006. Immediate and updated forecasting of aftershock hazard. Geophys. Res. Lett., 33, 10, L10305. Doi:10.1029/2006GL025888. Rashid H., 1991. Geography of Bangladesh, University Press Ltd, Bangladesh; 2nd edition, 545p. Reimann K.U., 1993. Geology of Bangladesh. Gerbruder Bornt Ramerg, Berlin, Germany, 160p. Siddique S., 2015. Gutenberg-Richter recurrence law to seismicity analysis of Bangladesh. IABSE-JSCE Joint Conference on Advances in Bridge Engineering-III, August 21-22, Dhaka, Bangladesh. Shi Y., and Bolt B.A., 1982. The standard error of the magnitude-frequency b-value. Bull. Seismol. Soc. Am., 72(5), 1667-1687. USGS, 2012. Earthquake Hazards Program. https://earthquake.usgs.gov/earthquakes/search/, USA, retrieved on 20 April 2017. Utsu T., 1999. Representation and analysis of the earthquake size distribution: a historical review and some new approaches. Pure Appl. Geophys., 155(2), 509-535. Wiemer S., and Wyss M., 2000. Minimum magnitude of complete reporting in earthquake catalogs: examples from Alaska, the western United States, and Japan. Bull. Seismol. Soc. Am., 90, 859-869. Doi:10.1785/0119990114. Woessner J., and Wiemer S., 2005. Assessing the quality of earthquake catalogues: Estimating the magnitude of completeness and its uncertainty. Bull. Seismol. Soc. Am., 95(2), 684-698. Doi:10.1785/012040007. Wyss M., Hasegawa A., Wiemer S., and Umino N., 1999. Quantitative mapping of precursory seismic quiescence before the 1989, M7.1 off-Sanriku earthquake, Japan. Annali Di Geoflsica, 42(5), 851-869. Zuniga F.R., and Wyss M., 1995. Inadvertent changes in magnitude reported in earthquake catalogs: Their evaluation through b-value estimates. Bull. Seismol. Soc. Am., 85, 1858-1866. .Zuniga F.R., and Wiemer S., 1999. Seismicity patterns: Are they always related to natural causes? Pure Appl. Geophys., 155(2), 713-726.